Emerging risks management in small and medium sized enterprise - Tuan Munirah, Tuan Nordin; Hanida, Abdul Aziz; Nur Fazrina, Mohamad Salleh; Mohd Azlan Fahmi, Mohd Azmi; Khairul Hamri, Ramli (AIP Publishing, 2023)
Following the changes from years to years, there are always new and upgraded technologies created and utilised in industries which then generates emerging risks to workers. To this recent, there are hardly studies conducted related to the management of emerging risks in SMEs in Malaysia. Therefore, this study aims to investigate the safety management applied for emerging risks in SMEs and to determine the significant differences between the size of enterprises and barriers in managing emerging risks. The study was conducted by distributing a self-administered questionnaire to 55 manufacturing SMEs in Malaysia. The data was then analysed by using SPSS software. From the survey, lack of OSH expert was considered as the main barrier with average percentage of 23.1% followed by complexity of legal obligations by 21.5%, lack of knowledge in OSH (20.5%), lack of financial resources (20%) and lack of training (18.7%). It shows that safety and health performance in SMEs are most influenced by the presence of OSH expertise. There is no significant differences between the size of enterprises and the barriers in managing emerging risks. This can be concluded that, both small and medium enterprises shared the same difficulties in managing emerging risks at their workplace.